Mechanistic insights into the clinical Y96D mutation with acquired resistance to AMG510 in the KRASG12C - Zhuang, Haiming; Fan, Jigang; Li, Mingyu; Zhang, Hao; Yang, Xiuyan; Lin, Ligen; Lu, Shaoyong; Wang, Qing; Liu, Yaqin (Frontiers in Oncology, 2022)
Special oncogenic mutations in the RAS proteins lead to the aberrant activation of RAS and its downstream signaling pathways. AMG510, the first approval drug for KRAS, covalently binds to the mutated cysteine 12 of KRASG12C protein and has shown promising antitumor activity in clinical trials. Recent studies have reported that the clinically acquired Y96D mutation could severely affect the effectiveness of AMG510. However, the underlying mechanism of the drug-resistance remains unclear. To address this, we performed multiple microsecond molecular dynamics simulations on the KRASG12C-AMG510 and KRASG12C/Y96D-AMG510 complexes at the atomic level. The direct interaction between the residue 96 and AMG510 was impaired owing to the Y96D mutation. Moreover, the mutation yielded higher flexibility and more coupled motion of the switch II and α3-helix, which led to the departing motion of the switch II and α3-helix. The resulting departing motion impaired the interaction between the switch II and α3-helix and subsequently induced the opening and loosening of the AMG510 binding pocket, which further disrupted the interaction between the key residues in the pocket and AMG510 and induced an increased solvent exposure of AMG510. These findings reveal the resistance mechanism of AMG510 to KRASG12C/Y96D, which will help to offer guidance for the development of KRAS targeted drugs to overcome acquired resistance.